Dog train leaving Fort McMurray, Alberta (Alice B. Donahue Library & Archives)
Four dog teams with sleds, Fort McMurray, Alberta. A note on the back reads: Dear Mr. Feuereisen: After eight days I managed to go through the Grand Rapids. The canoe capsized but I managed to rescue everything. The last five rapids I could manage in two days, but only with luck the Grand Rapids. I would be dead without any luck. Many greetings, Your Roland. photograph